Semi‐Mechanistic PK/PD Modeling and Simulation of Irreversible BTK Inhibition to Support Dose Selection of Tirabrutinib in Subjects with RA. Issue 2 (27th October 2021) - Meng, Amy; Humeniuk, Rita; Jürgensmeier, Juliane M.; Hsueh, Chia‐Hsiang; Matzkies, Franziska; Grant, Ethan; Truong, Hoa; Billin, Andrew N.; Yu, Helen; Feng, Joy; Kwan, Ellen; Tarnowski, Thomas; et al.
Abstract : Tirabrutinib is an irreversible, small‐molecule Bruton's tyrosine kinase (BTK) inhibitor, which was approved in Japan (VELEXBRU) to treat B‐cell malignancies and is in clinical development for inflammatory diseases. As an application of model‐informed drug development, a semimechanistic pharmacokinetic/pharmacodynamic (PK/PD) model for irreversible BTK inhibition of tirabrutinib was developed to support dose selection in clinical development, based on clinical PK and BTK occupancy data from two phase I studies with a wide range of PK exposures in healthy volunteers and in subjects with rheumatoid arthritis. The developed model adequately described and predicted the PK and PD data. Overall, the model‐based simulation supported a total daily dose of at least 40 mg, either q.d. or b.i.d., with adequate BTK occupancy (> 90%) for further development in inflammatory diseases. Following the PK/PD modeling and simulation, the relationship between model‐predicted BTK occupancy and preliminary clinical efficacy data was also explored and a positive trend was identified between the increasing time above adequate BTK occupancy and better efficacy in treatment for RA by linear regression.